Ters akımlı soğutma kulelerinde ısı ve kütle geçişinin incelenmesi - Sadıkoğlu, İ. Hakan (Fen Bilimleri Enstitüsü, 1996)
Hava şartlandırma sistemlerinde ve endüstriyel proseslerde her zaman için sistemden çekilmesi ve uzaklaştırılması gerekli bir ısı bulunmaktadır. Bir başka deyişle bir soğutma işlemine ihtiyaç vardır. Geçmişte bu işlem doğal bir su kaynağından veya şebekeden çekilen soğuk su ile gerçekleştiriliyordu. Bugün ise şebeke suyu ile bunu gerçekleştirmek pahalıya mal olmaktadır. Aynı şekilde soğutma suyunun doğal kaynaklardan çekilmeside nispeten zor olmakta ve ayrıca ekolojik dengeye zarar vermektedir. İşte bu noktada su soğutma kuleleri sistemdeki atik ısıyı uzaklaştırmak için ideal bir çözüm olmakta ve yukarıda belirtilen sorunların üstesinden gelmektedir.Bu çalışmada soğutma kulelerinden genel olarak bahsedilmekle birlikte,odak noktasını ters akımlı soğutma kuleleri oluşturacaktır. Ters akımlı soğutma kulelerinde ısı ve kütle geçişim irdelerken,teoriyi oluşturmak ve konuyu anlamayı kolaylaştırmak için3ölüm 2 ve 3 'de temel bağıntı ve kavramlar açıklanmıştır.Bu bölümlerde hava ve subuharın ideal gaz olarak kabul edeceğimizden karışımlar ve ideal gazlar anlatılmış,soğutma kulesindeki ısı ve kütle geçişini açıklayabilmek için birarada ısı ve kütle geçişi konusuna değinilmiştir. Daha sonra sırasıyla kütle geçiş katsayısı, Lewis bağıntısı, psikrometrik diyagram, bağıl ve özgül nem, adyabatik yaş termometre sıcaklıkları açıklanrmşur.Bölüm 4'de ASHRAE Handbook esas alarak soğutma kulelerinin çalışma prensipleri, tipleri ve tasarım esasları hakkında bilgi verilmiş ve kulede sis oluşumu açıklanmıştır. Son bölümde ısı ve kütle geçiş bağıntılarından faydalanarak, ters akımlı su soğutma kuleleri için ısı ve kütle geçiş teorisi çıkarılmış ve Merkel eşitliği elde edilmiştir.Buradan kule hacim hesabı için NTU(Number of Transfer Unit) değerini veren bir integral bağıntısı bulunmuştur. Daha sonra giriş ve çıkış şartlan verilen, örnek bir su soğutma kulesi için hacim ve kule yükseldiği hesabı yapılmıştır Bu hesap yapılırken NTU integrali Simpson 1/3 metodu kullanılarak sayısal olarak çözülmüştür.Bu amaçla FORTRAN 77 ile hazırlanmış basit bir bilgisayar programı bölüm sonunda verilmiştir.Aynı örnek problem daha sonra adım adım integrasyon metodu kullanılarak çözülmüş ve sayısal çözümle karşılaştırılmıştır. Daha sonra örnek kule için, kule hacminin yaş termometre sıcaklığı ve su/hava debileri oranı ile değişimi, grafik olarak sunulmuş ve açıklanmıştır.

Heat and Mass Transfer Analysis of Counterflow Cooling Towers Most air-conditioning systems and industrial processes generate heat that must be removed and dissipated. Water is commonly used as a heat transfer medium to remove heat from refrigerant condensers or industrial process heat exchangers. In the past, this was accomplished by drawing a continuous stream of water from a natural body of water ot a utility water supply, heating it as it passed through the process, and then discharging the water directly to sewer or returning it to the body of water. Water purchased from utilities for this purpose has now become prohibitively expensive because of increased water supply and disposal costs. Similarly, cooling water drawn from natural sources is relatively unavailable because the increased temperature of the discharge water disturbs the ecology of the water source. Air-cooled heat exchangers may be used to cool the water by rejecting heat directly to the atmosphere, but the first cost and fan energy consumption of these devices are high. Cooling towers overcome most of these problems and, as such, are commonly used to dissipate heat from water-cooled refrigeration, air-conditioning, and industrial process systems. A cooling tower cools water by a combination of heat and mass transfer. The water to be cooled is distributed in the tower by spray nozzles, splash bars, or filming- type fill, which exposes a very large water surface area to atmospheric air. Atmospheric air is circulated by (1) fans, (2) convective currents, (3) natural wind currents, or (4) induction effect from sprays. A portion of the water absorbs heat to change from a liquid to a vapor at constant pressure. This heat of vaporization at atmospheric pressure is transferred from the water remaining in the liquid state into the airstream. The temperature difference between the water entering and leaving the cooling tower is the range. For a system operating in a steady state, the range is the same as the water temperature rise through the load heat exchanger, provided the flow rate through the cooling tower and heat exchanger are the same. Accordingly, the range is determined by the heat load and water flow rate, not by the size or capability of the cooling tower. IX The difference between the leaving water temperature and the entering air wet-bulb temperature is the approach to the wet bulb or simply the approach of the cooling tower. The approach is a function of cooling tower capability, and a larger cooling tower produces a closer approach ( colder leaving water ) for a given heat load, flow rate, and entering air condition. Thus, the amount of heat transferred to the atmosphere by the cooling tower is always equal to the heat load imposed on the tower, while the temperature level at which the heat is transferred is determined by the thermal capability of the cooling tower and the entering wet-bulb temperature. The thermal performance of a cooling tower depends principally on the entering air wet-bulb temperature. The entering air dry-bulb temperature and relatively humidity, taken independently, have an insignificant effecet on fliermal performance of mechanical-draft cooling towers, but they do affect the rate of water evaporation within the cooling tower. The thermal capability of any cooling tower may be defined by tile fblowing parameters : 1. Entering and leaving water temperatures 2. Entering air wet-bulb or entering air wet-bulb and dry-bulb temperatures 3. Water flow rate The entering air dry-bulb temperature affects the amount of water evaporated from the water cooled in any evaporative-type cooling tower. It also affects m flow through hyperbolic towers and directly establishes thermal capability within any indirect-contact cooling tower component operating in a dry mode. The thermal capability of cooling towers for air conditioning is identified in nominal capacity, based on heat dissipation of 1.25 kw per condenser kilowatt and a water circulation rate of 54 mL/s per kilowatt cooled from 35°C to 29.4 ° C wet-bulb temperature. For specific applications, however, nominal capacity ratings are not used, and the thermal performance capability is usually stated in terms of flow rate at specified operating conditions ( entering and leaving water teperatures and entering air wet-bulb and/or dry-bulb temperatures ). According to the location of th fan corresponding to the fill and to the flow arrangements of air and water, currently widely used mechanical draft cooling towers for HVAC&R can be classified into the following categories:. Counterflow induced draft. Crossflow induced draft. Counterflow forced draft Counterflow Induced Draft Cooling Towers In a counterflow induced draft cooling tower, the fan is located downstream from the fill at the air exit. Atmospheric air is drawn by the fan through the intake louver or, more simply, an opening covered by wire mesh. Cooling water from the condenser or recirculating water from the coil, or a mixture of the two is evenly sprayed or distributed over the fill and falls down into the water basin. Air is extracted across the fill and comes in direct contact with the water film. Because of the evaporation of a small portion o the cooling water, usualy about 1 percent of the water flow, the temperature of the water gradually decreases as it falls down through the fill countercurrent to the exracted air. Evaporated water vapor is absorbed by the airstream. Large water droplets entrained in the airstream are collected by the drift eliminators. Finally, the airstream and drift are discharged at the top exit. The evaporatively cooled water falls into the water basin and flows to the condenser. In a counterflow induced draft cooling tower, the driest air contacts the coldest water. Such a counterflow arrangement shows a better tower performance than a crossflow arrangement. In addition, air is drawn through the fill more evenly by the induced draft fan and is discharged at a higher velocity from the top fan outlet. Both higher exhaust air velocity and even velocity distribution reduce the possibility of exhaust air recirculation. Crossflow Induced Draft Cooling Towers In a crossflow induced draft cooling tower, the fan is also located downstream from the fill at the top exit. The fill is installed at the same level as the air intake. Air enters the tower from the side louvers and moves horizantally through the fill and the drift eliminator. Air is then turn upward and finally discharged at the top exit. Water sprays from the nozzles, falls across the fill, and forms a crossflow arrangement with the airstream. The crossflow induced draft cooling tower has a greater air intake area. Because of the crossflow arrangement, th tower can be considerably lower than the counterflow tower. However, the risk of recirculation of tower exhaust air increases. Counterflow Forced Draft Cooling Towers In a counterflow forced draft cooling tower, the fan is positioned at the bottom air intake, that is, on the upstream side of the fill. Cooling water sprays over the fill from the top and falls down to the water basin. Air is forced across the fill and comes in direct contact with the water. Because of the evaporation of the water, its temperature gradually decreases as it flows down along the fill in a counter-flow arrangement with air. In the airstream, large water droplets are intercepted near the air exit by the eliminator. Finally, the airstream containing drift is discharged at th top opening. Because the fan is located near the ground level, the vibration of the counterflow forced draft tower is small compared with that of the induced draft tower. Also, if the centrifugal fan blow toward the water surface, there is a better evaporative cooling effect over the water basin. However, the disadvantages of this type of cooling tower are the uneven distribution of air flowing through the fill, which is caused by the forced draft fan. In addition, the high intake velocity may xi recapture a portion of the warm and humid exhaust air. Counterflow forced draft cooling towers are often used in small and medium installations. Materials of Construction Materials found in cooling tower costruction are usually selected to resist the corrosive water and atmospheric conditions. Wood. Wood has been used extensively for all static components except hardware. Redwood and fir predominate, usually with postfabrication pressure treatment of waterborne preservative chemicals, typically chromated-copper-arsenate (CCA) or acid-copper-chromate (ACC). These microbiocide chemicals prevent the attact of wood-destructive organisms, such as termites or fungi. Metals. Steel with galvanized zinc is used for small-and medium-size installations. Hot-dip galvanizing ?fter fabrication is used for larger weldments. Hot- dip galvanizing and cadmium and zinc plating are used for hardware. Brasses and bronzes are selected for special hardware, fittings, and tubing material. Stainless steels (principally 302, 304, and 316) are often used for sheet metal, drive shafts, and hardware in exceptionally corrosive atmospheres. Cast iron is a common choice for base castings, fan hubs, motor or gear reduction housings, and piping-valve components. Metals coated with polyurethane and polyvinyl-chloride are used selectively for special components. Epoxy-coal tar compounds and epoxy-powdered coatings are also used fbr key components or entire cooling towers. Plastics. Fiberglass-reinforced polyester materials are used for components such as piping, fan cylinders, fan blades, casing, louvers, and structural connecting components. Polypropylene and ABS are specified for injection-molded components, such as fill bars and flow orifices. PVC is increasingly used as fill, eliminator, and louver materials. Reinforced plastic mortar is used in larger piping systems, coupled by neoprene O-ring-gasketed ball and socket joints. Concrete, masonry, and tile. Concrete is typically specified for cold-water basins of fielderected cooling towers and is used in piping, casing, and structural systems of the largest towers, primarily in the tower industry. Special titles and masonry are used when aesthetic considerations are important. The basic theory of cooling tower operation was first proposed in 1923 by Walker et al. However, the first practical use of the differential equations was developed by Merkel in 1925. He combined the equations for heat and water vapor transfer and used enthalpy as the driving force to allow for both sensible and latent heat transfer. Heat is removed from the water by a transfer of sensible heat due to a difference in temperature levels and by the latent heat equivalent of the mass transfer resulting from the evaporation of a portion of the circulating water. Merkel combined these into a single process based on enthalpy difference as the driving force. The theory used by Merkel requires two main assumptions, namely, that the water loss by evaporation is neglected and that the Lewis number for air/water vapor systems is unity. The theory states that all of the heat transfer taking place at any xii position in the tower is proportional to the difference between the enthalpy of air saturated at the temperature of the water at that point in the tower. Quantative treatment of cooling tower performance by dealing with heat and mass transfer separately is very laborious. Therefore the simplifying approximation of MerkeFs enthalpy theory has been almost universally adopted for the calculation of tower performance. MerkeFs differential equation for the cooling tower was redeveloped by Nottage and converted to a graphical method of solution by Lichtenstein. Another graphical prosedüre, for determining the air process line in a cooling tower, was suggested by Mickley. Simpson and Sherwood carried out experimental studies on several small-scale cooling towers, and examined the dependence of the mass transfer coefficient on the various air and water properties. Carey and Williamson extended MerkeFs theory to be applicable to gas cooling and humidification, and proposed the Stevens diagram (devised by W.L.Stevens ) for the solution of the cooling tower integral necessary for determining the required volume of a tower. Baker and Shryock reviewed MerkeFs work and examined the effects of some of the approximations. Further theoritical work on cooling towers has been carried out by Berman, Hsu et al., Threlkeld, Yadigaroglu and Pastor, and Whiller. Extensive sets of curves for cooling tower design, based on MerkeFs theory, have been prepared by the American Society of Heating, Refrigerating and Air Conditioning Engineers. In this study, heat and mass transfer theory of counterflow cooling towers are presented. The performance of counterflow cooling towers is analyzed by applying by so-called Merkel model. This model is based on equations developed in a paper published in German by Merkel (1925). The equations express an energy balance and describe simultaneous mass and heat transfer coupled through the Lewis relation. However, in the interest of tractibility the equations were simplified by omitting a term and as a result do not account for the mass of water lost by evaporation. Given the inlet water and air conditions the Merkel equations predict the enthalpy (hence wet-bulb temperature ) of the outlet air, but not its humidity. The equations also predict the required number of transfer units (NTU) to accomplish the process.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: enerji; ısı geçişi; kütle aktarımı; soğutma kuleleri; energy heat transfer; mass transfer; cooling towers